Effects of glyphosate and cylindrospermopsin at environmental concentrations on growth, photosynthesis and mineral content in lettuce plants - Sengupta, Soumi (2019)
Glyphosate is the most widely used herbicide, mainly due to the extensive cultivation of glyphosate resistant plants. The intensification of agriculture has increased water eutrophication and the presence of natural cyanobacterial toxins, such as ylindrospermopsin. Previous studies support the hypothesis that glyphosate and cylindrospermopsin can affect the yield of crop plants, depending on the exposure concentration. Lettuce (Lactuca sativa L.)